Triple sexually transmitted infections among pregnant woman in the context of Elimination of mother to child transmission in Southern Ethiopia: Reports from a survey of questionnaires and laboratory studies. - Israel, Eskinder; Hizkel, Iskindir; Geta, Temesgen; Feleke, Tihun; Samuel, Beniyam; Markos, Desta (Frontiers in Global Women's Health, 2023)
Background: Sexual transmitted infections (STI) always result in a wide range of health problems if left untreated. It leads to an adverse birth outcomes, including stillbirth, fetal loss, neonatal death, premature and low birth-weight. Although great effort has been made to reduce STIs nationally, their incidence remains high in Ethiopia and, their synergism combined with other factors in the country, calls for urgent action. Therefore, this study aimed to identify the determinants of triplex STIs among pregnant women attending antenatal care (ANC) in sawula town public health facilities, Gofa, Southern Ethiopia. Methods: A cross-sectional study design was conducted among a total of 484 pregnant women attending ANC in sawula town public health facilities, southern Ethiopia from May to July, 2022. Data were collected from pregnant women's serum using HIV-rapid test, HBsAg Rapid Test Device, and VDRL for HIV, HBV, and Syphilis respectively. Descriptive statistics such as frequency and percentage were used to describe each relevant variable. Logistic regression analyses were used to identify determinants of STIs. Results: A total of 484 pregnant women attending antenatal care was reviewed. The mean age of women was 24.0 ± (SD 4.6 years) and 191 (40.7%) women completed their secondary education and above. The overall Seroprevalance of triplex STI (HIV, HBV, and Syphilis) among pregnant women was 6.8%. Pregnant women who were not able to read and write (AOR= 4.1, 95% CI= 2.3-24.3), history of tattooing (AOR= 5.2, 95% CI= 1.8-11.3), history of abortion (AOR= 2.7, 95% CI= 1.3-5.5), and history of multiple sexual partners (AOR= 5.2, 95% CI= 2.1-14.4) were associated with STI among pregnant women. Conclusion: Our study showed that determinants which were identified by our study to be highly associated with STIs can substantially be improved by strengthening the existing health education and promoting primary education to bring further behavioral change.